2002
DOI: 10.1034/j.1600-0773.2002.910605.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Models for Cholecystokinin‐A Receptor

Abstract: Numerous techniques have been used to elucidate the structural basis for interaction of cholecystokinin (CCK)-related peptides with their hormone-binding receptor, the CCK-A receptor (CCK-AR), including structure-activity relationship studies, site-directed mutagenesis, photoaffinity-labeling, and solution NMR analysis of both CCK peptide ligands and peptide fragments derived from the CCK-A receptor. Different structural models have been developed for the peptide-receptor complexes using various subsets of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…This set of data strongly supports differences in conformation of these two closely related receptors. This is also consistent with the distinct modes of docking the same CCK peptides to both receptors that has been proposed previously (Dawson et al, 2002;Miller and Gao, 2008).…”
Section: Allosteric Cck1r Antagonist Radioligandsupporting
confidence: 77%
“…This set of data strongly supports differences in conformation of these two closely related receptors. This is also consistent with the distinct modes of docking the same CCK peptides to both receptors that has been proposed previously (Dawson et al, 2002;Miller and Gao, 2008).…”
Section: Allosteric Cck1r Antagonist Radioligandsupporting
confidence: 77%
“…Like other members of the G-protein-coupled receptor superfamily, CCK1R has a heptahelical transmembrane (TM) structure (4,24,91,143) (Fig. 3).…”
Section: Cck Receptor In Different Animal Speciesmentioning
confidence: 99%
“…We previously employed this biophysical approach to evaluate the environment of Alexa within a CCK-8-like analogue, Alexa 488 -Gly-[(Nle 28,31 )CCK-26 -33] (CCK-8 probe), bound to the type A CCK receptor (1). Our data demonstrated that conformational changes associated with activation of that receptor cause the amino terminus of bound CCK to move into an aqueous milieu from its more protected environment.…”
mentioning
confidence: 99%